Ruxolitinib cream monotherapy demonstrates rapid improvement in the extent and signs of mild to moderate atopic dermatitis across head and neck and other anatomic regions in adolescents and adults: pooled results from 2 phase 3 studies - Eric L. Simpson; Robert Bissonnette; Zelma C. Chiesa Fuxench; Howard Kallender; Daniel Sturm; Haobo Ren; Linda F. Stein Gold (Taylor & Francis Group, 2024)
AbstractPurpose: Ruxolitinib (selective Janus kinase [JAK] 1 and JAK2 inhibitor) cream demonstrated efficacy and safety in patients with atopic dermatitis (AD) in the phase 3 TRuE-AD studies. In TRuE-AD1/TRuE-AD2 (NCT03745638/NCT03745651), adults and adolescents with mild to moderate AD were randomized to apply twice-daily ruxolitinib cream or vehicle for eight weeks. Here, we evaluated the efficacy and tolerability of ruxolitinib cream by anatomic region, focusing on head/neck (HN) lesions that are typically difficult to manage and disproportionately affect quality of life (QoL).Materials and methods: Eczema Area and Severity Index (EASI) responses in anatomic regions were evaluated in the pooled population (N = 1208) and among patients with baseline HN involvement (n = 663). Itch, Investigator's Global Assessment (IGA), QoL, and application site tolerability were also assessed.Results: By Week 2 (earliest assessment), ruxolitinib cream application resulted in significant improvements across all EASI anatomic region subscores and AD signs versus vehicle, with further improvements through Week 8. Significantly more patients with HN involvement who applied ruxolitinib cream versus vehicle achieved clinically meaningful improvements in itch, IGA, and QoL. Application site reactions with ruxolitinib cream were infrequent (<3%), including in patients with HN involvement.Conclusions: These results support the use of ruxolitinib cream for AD treatment across all anatomic regions, including HN.